The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Mapping and Politics in the Digital Age 2018
DOI: 10.4324/9781351124485-3
|View full text |Cite
|
Sign up to set email alerts
|

From the cartographic gaze to contestatory cartographies

Abstract: Rene Descartes declared in the 16 th Century that the world was now dominated by the visual, a notion that would be seen as defining the Enlightenment (Descartes, cited in Potts, 2015). As the increased dominance of seeing and the desire to visualise the world cohered with the production of increasingly accurate tools of measurement and the advent of the printing press, cartography emerged as a discipline, often used as tool of oppression and dominance. Cartographic visualizations, afforded the creator, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A key example of the presentation of data is processes of mapping, now viewed as a vital tool in humanitarian responses to crises, where geotagged photographs, social media posts, aerial imagery from drones, and other forms of data are used to piece together documentation of communities in need (Specht, 2020). These maps present themselves as accurate and objective pictures of reality while being projections from a specific vantage point (Specht and Feigenbaum, 2018). Maps are used to present needs and document humanitarian impacts and responses.…”
Section: The Presentation and Instrumentalisation Of Humanitarian Datamentioning
confidence: 99%
“…A key example of the presentation of data is processes of mapping, now viewed as a vital tool in humanitarian responses to crises, where geotagged photographs, social media posts, aerial imagery from drones, and other forms of data are used to piece together documentation of communities in need (Specht, 2020). These maps present themselves as accurate and objective pictures of reality while being projections from a specific vantage point (Specht and Feigenbaum, 2018). Maps are used to present needs and document humanitarian impacts and responses.…”
Section: The Presentation and Instrumentalisation Of Humanitarian Datamentioning
confidence: 99%
“…54-57) illustrates how the platforms, symbols, metrics and schemes used by digital humanitarians tend to rely on certain types of knowledge production and misrepresent other forms of knowledge production, like "collective memory," "affective geographies," or indigenous representations of nature that do not conform to "Cartesian space." Though digital maps show multi-layered, reliable, and upto-date information with unprecedented concreteness and dynamism, critics note that information is still remote from indigenous practices and cosmologies (Specht & Feigenbaum, 2019).…”
Section: The Limits Of All-seeing Digital Maps: the Partial Representation Of Lifementioning
confidence: 99%
“…The authors in this issue found themselves confronted with the traditional cartographic order of the world that has forced many peoples into an imperial logic under the no-win situation often referred to as Map or Be Mapped (Paglen, 2008). Both Kent (2018, this issue) and Duggan (2018, this issue) grapple with the notion that cartography is not only poor at describing the qualities of the relationships of everyday life, but also forms power traditionally being used as an instrument of both colonialism and the contemporary geopolitical ordering of the world (Specht and Feigenbaum, 2018;Paglen, 2008). These issues are both alleviated and compounded by the growth in the number of privately owned sensors, not only harnessing Global Positioning Systems (GPS), but also sound-level, light and accelerometer sensors.…”
mentioning
confidence: 99%